2016
DOI: 10.1186/s12955-016-0567-7
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between weight status and health-related quality of life in Chinese primary school children in Guangzhou: a cross-sectional study

Abstract: BackgroundTo investigate the association between weight status and health-related quality of life (HRQOL) among pupils in Guangzhou, China.MethodsThe study comprised 5781 children aged 8–12 years from 29 schools. Height and weight were objectively measured using standardized methods, and BMI z-score derived using the age and sex specific WHO reference 2007 for 5–19 years. Weight status was classified as underweight (<−2SD), healthy weight (between -2SD and 1SD), overweight/obesity (>1SD). HRQOL was measured by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 41 publications
(50 reference statements)
3
23
2
2
Order By: Relevance
“…Although the symptoms incurred from myopia or abnormal weight might be minor compared to those from severe conditions such as acute lymphoblastic leukemia, this yet implies the EQ-5D-Y may not be sensitive to them, which is similar to the findings reported in previous studies [8,16]. Indeed, studies using the PedsQL 4.0 in China found that the two conditions did have significant lower HRQOL scores than healthy children and adolescents in one or several aspects [24,30]. Hence, it has to be used with caution in children and adolescents with minor or no health conditions.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Although the symptoms incurred from myopia or abnormal weight might be minor compared to those from severe conditions such as acute lymphoblastic leukemia, this yet implies the EQ-5D-Y may not be sensitive to them, which is similar to the findings reported in previous studies [8,16]. Indeed, studies using the PedsQL 4.0 in China found that the two conditions did have significant lower HRQOL scores than healthy children and adolescents in one or several aspects [24,30]. Hence, it has to be used with caution in children and adolescents with minor or no health conditions.…”
Section: Discussionsupporting
confidence: 77%
“…We also examined the difference in frequency between groups known to be different in health status. The groups included: 1) those with and without myopia; 2) those who were underweight, normal weight, and overweight according to BMI level [30]. The EQ-5D-Y may not differentiate the differences between the groups given the nature of the two conditions and study samples [8,16].Chi-square or Fisher's exact test were performed whenever appropriate to test whether there were statistically significant difference between the groups in the percentage; and the categories 'some' and ' a lot of' were collapsed to a single category ('any problem').…”
Section: Discussionmentioning
confidence: 99%
“…However, the evidence supporting an association in population-based samples has remained inconclusive. A large number of relevant population-based studies have shown a significant inverse association between obesity and HRQoL, particularly in the physical, social and school domains [79]. However, other studies have found no associations between weight status and HRQoL [1012].…”
Section: Introductionmentioning
confidence: 99%
“…Другое исследование, проведенное в Кувейте и спланированное, подобно представленному на парных выборках, показало, что ожирение затрагивает СÇКЖ детей только в области физического функционирования [27]. Еще два исследования, проведенные в Китае (Гуанчжоу), показали, что за исключением в одном из них школьного [28], а в другом социального [29] функционирования, ожирение не имело значимого влияния на СÇКЖ. Можно заметить, что все упомянутые исследования не включали детей европеоидных ýтносов, поýтому логичным объяснением наших находок может быть влияние на восприятие избыточного веса культурных традиций того или иного ýтноса.…”
Section: Discussionunclassified